Amino Acid Based Antimicrobial Agents – Synthesis and Properties. (1st October 2021) - Nowak, Michał G.; Skwarecki, Andrzej S.; Milewska, Maria J.
Abstract: Structures of several dozen of known antibacterial, antifungal or antiprotozoal agents are based on the amino acid scaffold. In most of them, the amino acid skeleton is of a crucial importance for their antimicrobial activity, since very often they are structural analogs of amino acid intermediates of different microbial biosynthetic pathways. Particularly, some aminophosphonate or aminoboronate analogs of protein amino acids are effective enzyme inhibitors, as structural mimics of tetrahedral transition state intermediates. Synthesis of amino acid antimicrobials is a particular challenge, especially in terms of the need for enantioselective methods, including the asymmetric synthesis. All these issues are addressed in this review, summing up the current state‐of‐the‐art and presenting perspectives fur further progress. Abstract : Structures of several dozen known antibacterial, antifungal or antiprotozoal agents are based on an amino acid scaffold. In most of them, the amino acid skeleton is crucial for antimicrobial activity, as very often they are structural analogs of amino acid intermediates of various microbial biosynthetic pathways. Synthesis of amino acid antimicrobials is a particular challenge, especially in terms of the need for enantioselective methods, including asymmetric synthesis.